MOLECULAR DIVERSITY OF SECONDARY METABOLITE-PRODUCING MARINE MICROORGANISMS ASSOCIATED WITH INDONESIAN REEFS INVERTEBRATES - Radjasa, Ocky Karna; Sabdono, Agus (Marine Research in Indonesia, 2008)
The metabolites from microorganisms are a rapidly growing field, due to the suspicion that a number of metabolites obtained from reefs invertebrates are produced by associated microorganisms. Less than 2% of microbial flora has been successfully isolated from marine environment. Coral reefs are the most diverse marine ecosystems, however, little is known about the microbial diversity in these ecosystems. It is expected that still quite a few parts of unexplored culturable invertebrate-associated microorganisms exists in the reef environments. The present study aimed at estimating the biodiversity of secondary metabolite-producing microbes associated with reefs invertebrates such as coral, soft coral and sponge collected from geographically different areas.